Impacts of the implementation of Industry´s 4.0 technologies in the portuguese footwear industry - Silva, Francisca Gomes (2020)
The first three industrial revolutions came about as a result of mechanization, electricity and IT. It is safe to state that a fourth revolution is currently taking place in manufacturing, with it being generally branded as Industry 4.0. These Cyber-Physical Systems comprise smart machines, storage systems and production facilities capable of autonomously exchanging information, triggering actions and controlling each other independently. The present investigation takes this premise into account and focuses in pursuing what are the main implications of the implementation of Industry´s 4.0 technologies in the Portuguese Footwear Industry. In order to lay the foundations for the study, an extensive literature review was executed. This was followed by a qualitative and exploratory investigation, based on twelve interviews with various relevant actors of the Portuguese footwear scene. The interviews resulted in insightful conclusions. Firstly, it is possible to notice that the Portuguese Footwear industry is generally well equipped and informed. Generally, the manufacturers are aware of the new technologies that are made available, being that there are already successful examples of companies using them. The study has highlighted the importance for companies to develop an extensive evaluation regarding their specific needs in order to better decide in which technologies to invest. The path is being designed in order to continuously simplify technologies, so that they are easier to work with. The main constraint, to the present day, is linked with finding skilled workforce to perform tasks at the shop floor level and also with the generation of enough value that allows the manufacturers to invest in more advanced technology.